2016
DOI: 10.1590/s1984-82502016000100018
|View full text |Cite
|
Sign up to set email alerts
|

Critical analysis: use of polymerase chain reaction to diagnose leprosy

Abstract: Leprosy is a neglected tropical disease and an important public health problem, especially in developing countries. It is a chronic infectious disease that is caused by Mycobacterium leprae, which has a predilection for the skin and peripheral nerves. Although it has low sensitivity, slit-skin smear (SSS) remains the conventional auxiliary laboratory technique for the clinical diagnosis of leprosy. Polymerase chain reaction (PCR) is a molecular biology technique that holds promise as a simple and sensitive dia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 23 publications
0
10
0
Order By: Relevance
“…Martinez et al (2011) reported highest RLEP sensitivity (81%) as compared to other three PCR markers [34]. Maltempe et al (2016) reported RLEP PCR on SSS to be equally sensitive as AFB smear microscopy (24%) [28], which is the lowest (data not shown). Yan et al (2014) reported at least 72% of RLEP PCR positivity as compared to 35% on smear microscopy of paraffin-embedded biopsies among PB leprosy cases [36].…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Martinez et al (2011) reported highest RLEP sensitivity (81%) as compared to other three PCR markers [34]. Maltempe et al (2016) reported RLEP PCR on SSS to be equally sensitive as AFB smear microscopy (24%) [28], which is the lowest (data not shown). Yan et al (2014) reported at least 72% of RLEP PCR positivity as compared to 35% on smear microscopy of paraffin-embedded biopsies among PB leprosy cases [36].…”
Section: Resultsmentioning
confidence: 97%
“…De Wit et al (1993) reported on the utility of PCR for detection of M. leprae in nasal swab specimens amplifying the 531-bp pra gene, demonstrating 79.6% positivity of PCR [22]. Kyeong-Han Yoon reported PCR on slit skin samples, which was subsequently reported by many others [23,24,25,26,27,28]. PCR on biopsies has been reported by Wichitwechkarn et al (1995), with a mean PCR positivity of 66% and subsequently by many others.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, the loop-mediated isothermal amplification assay performed better than the reported polymerase chain reactionbased molecular tests that exhibited a sensitivity of approximately 76%. 14,17 Furthermore, 8 out of 11 (72.7%) slit aspirates from paucibacillary patients tested positive for M. leprae as compared to two out of 11 (18.2%) by routine microscopy. Thus, based on the results observed in paucibacillary patients, our loop-mediated isothermal amplification assay can indeed be advantageous for detecting M. leprae in the early stage of the disease which could be crucial in controlling disease transmission.…”
Section: Discussionmentioning
confidence: 96%
“…The highly conserved repetitive sequence RLEP has been the preferred target due to its high copy number (n = 37), 10,14 although other targets such as rpoT, 16S rRNA and Sod A have also been exploited for detection of M. leprae by polymerase chain reaction/ quantitative polymerase chain reaction. 16,17 Several cost-effective isothermal amplification-based techniques have emerged to substitute expensive molecular methods. 18 Amongst these, loop-mediated isothermal amplification is simple, rapid, specific and sensitive and only a heating block or water bath capable to maintain a constant temperature (60 C to 65 ºC) is required.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, the advances in M. leprae structural and functional genomics has allowed the development of highly specific PCR-based gene amplification assays for early rapid M. leprae DNA detection with high sensitivity. PCR has also proved useful in the M. leprae viability determination, identification of routes of transmission and leprosy drug resistance ( Geluk et al, 2012 ; Martinez et al, 2014 ; Soto and Muñoz, 2015 ; Maltempe et al, 2016 ).…”
Section: Current Status Of Known Biomarkers For Diagnostic Assaysmentioning
confidence: 99%